Insight into the role of WO3 on catalytic performance over CuO-CeO2 catalyst for NH3 selective catalytic oxidation reaction. Issue 6 (December 2021) - Yang, Xiaoli; Li, Na; Zhang, Yiqiu; Li, Morui; Liu, Mo; Tian, Zimeng; Zhang, Qiulin; Chen, Jianjun
Abstract: CuO-CeO2 catalysts modified with WO3 were prepared by a sol-gel method and applied in selective catalytic oxidation (SCO) of NH3 to N2 . It can be found that the NH3 conversion showed a gradually decreased trend but the N2 selectivity monotonically increased with the WO3 introduced. As evidence from H2 -TPR and Raman measurements, the doping of WO3 resulted in a decrease in the concentration of oxygen vacancy and thereby reduced the redox ability of Cu-Ce, which was not helpful for the conversion of NH3 . However, NH3 -TPD and in situ DRIFTS results showed that WO3 introduction can significantly enhance the density of Brønsted acid sites on the catalyst and thereby promote the adsorption of NH3 molecules. Typically, CuO-CeO2 doping with 15 wt% WO3 (Cu-Ce-15W) presented the highest NH3 storage capacity. This could suppress the over-oxidation of NH3 and thus make contribution to the enhancement of N2 selectivity. This work could help to engineer highly efficient catalysts for NH3 -SCO reaction. Graphical Abstract: ga1 Highlights: CuO-CeO2 catalysts modified with WO3 were prepared by a sol-gel method. Cu-Ce-W catalysts exhibited excellent NH3 -SCO performance at 200–300 °C. Enhanced acidity contributed to the superior N2 selectivity over Cu-Ce-W. The doping of WO3 resulted in a decrease in the concentration of oxygen vacancy. Cu-Ce-W catalysts could suppress the over-oxidation of NH3 and thus make contribution to the enhancement of N2 selectivity.